Lets say the numbers are x and y. The two equations are:

x+y=44

x= 3y-2

Next you use substitution for x in the first equation which brings you to 3y-2 + y = 44 which simplyfies to:

4y - 2 = 44

4y = 46

**y = 11.5**

Then you...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Lets say the numbers are x and y. The two equations are:

x+y=44

x= 3y-2

Next you use substitution for x in the first equation which brings you to 3y-2 + y = 44 which simplyfies to:

4y - 2 = 44

4y = 46

**y = 11.5**

Then you plug back y=11.5 in either of the equation to solve for x:

x = 3y - 2

x = 3(11.5) - 2

**x = 32.5**

Translate into equations x is one number y is the other. Let's say y is the larger number.

x+y=44

and

y=3x-2

Using substitution we get

x+3x-2=44

4x=46

x=11.5

y=44-x=32.5

check 3(11.5)-2=34.5-2=32.5

So the two numbers are 11.5 and 32.5